A Mixed Objective Assignment Problem. (November 2019) - Ramesh, P.; Abdul Razak, K.
Abstract: A general assignment problem includes N tasks that intend assign to N workers to what place each laborer has the sufficiency to do all tasks. The objective is to confront the optimum assignment of a number of tasks (jobs) to an enlarge number of services (or persons) at a minimum cost. In this freebie the objectives are proposed as mixed objective which is triangular fuzzy number. Yager's ranking approach has been used for grade the fuzzy numbers. The Hungarian method is used to solve the problem. The results of the numerical example prove that a fine conciliation solution can be reached effectively.